Patent Litigation Risk and Firm Boundaries - Wu, Fan (Production and Operations Management, 2026)
The increasing prevalence of patent infringement litigation in recent decades has imposed significant costs on firms. This paper empirically examines how this legal risk influences a key operational decision: vertical integration. Drawing on the real options theory (ROT), we argue that managers reduce the extent of vertical integration to preserve flexibility and make operational adjustments in anticipation of unfavorable outcomes from patent lawsuits. Using a dataset of public firms and a text-based measure of vertical integration, our findings show that firms facing higher patent litigation risk are less vertically integrated. At the same time, these firms maintain broader supplier networks and product market scopes, consistent with a preference for leveraging market mechanisms to reduce the costs of exercising switch and exit options. The negative relationship between litigation risk and vertical integration is particularly pronounced in durable goods sectors and declining industries, where the ability to divest or halt operations is highly valued. Additionally, we find that firms diversify their supplier base and product and technology portfolios after facing patent lawsuits. However, more vertically integrated firms are slower to make these adjustments, suggesting that they encounter greater friction in exercising real options. Overall, our study highlights the significant role that intellectual property disputes play in shaping corporate vertical integration strategies.